Extended working lives? The meaning of working to older university workers in Australia. (19th July 2006) - Shacklock, Kate
This paper reports the findings of a study of older university workers (both academic and general/administrative staff) in Australia on the meaning of working to them as individuals. The findings from the qualitative research suggest that working is important and enjoyable for older workers, but 'family' is more important than 'working'. The meaning of working differs between older workers and is influenced by their differing work characteristics, especially autonomy, flexibility and variety. Such perceptions impact upon their intentions to continue working, with most older workers wanting to retire before the traditional age of 65 years. Differences between the participant categories are noted and explanations offered. The evidence suggests directions for HRM practitioners and policymakers to increase the retention of older workers, who are needed to meet a predicted shortfall of skilled workers in Australia.